Eksplorasi Technological Pedagogical Content Knowledge (TPACK) Mahasiswa Calon Guru Kimia - Ruli Meiliawati; Alfred Tobok Siahaan; Suandi Sidauruk (Jurnal Ilmiah Kanderang Tingang, 2023)
Student teacher candidates (chemistry) must have adequate Technological Pedagogical Content Knowledge (TPACK) competence, because TPACK is in the realm of the four main competencies of a teacher which include pedagogical competence, personality competence, social competence and professional competence which are useful in implementing learning. This study aims to explore the TPACK of prospective chemistry teachers. TPACK is a framework that tries to understand the relationship between lesson material (Content), knowledge about teaching (pedagogical knowledge), and the use of technology (technological knowledge). In TPACK, prospective teacher students' knowledge of integrating technology in learning makes classroom activities effective and efficient. Technology integration is considered a closely related teaching component and is also included in PCK. This research used a cross-sectional survey method with 36 chemistry education students who had carried out PPL as participants. The research results indicate that several prospective chemistry teacher students have sufficient TPACK competency. However, the use of technology, mastery of material, and pedagogical skills still need to be improved in order to produce professional teachers.